Local languages, local Malay, and Bahasa Indonesia; A case study from North Maluku - Bowden, John (UI Scholars Hub, 2012)
Many small languages from eastern Indonesia are threatened with extinction. While it is often assumed that 'Indonesian' is replacing the lost languages, in reality, local languages are being replaced by local Malay. In this paper I review some of the reasons for this in North Maluku. I review the directional system in North Maluku Malay and argue that features like the directionals allow those giving up local languages to retain a sense of local linguistic identity. Retaining such an identity makes it easier to abandon local languages than would be the case if people were switching to 'standard' Indonesian.